STUDY OF MATERIALS AND WELDING USED IN THE CONSTRUCTION OF RACKS FOR STORAGE OF FUEL ELEMENTS AT NUCLEAR PLANTS - Ribeiro, A. A. F.; Ferreira, C. A. M.; Souza, M. C. L.; Tapanes, N. C. O. (Revista de Engenharia Térmica, 2021)
This paper showed the technological innovations and the necessary requirements for the welding of ASTM A240 TP316L Austenitic Stainless Steel in the construction of racks used in the storage of Fuel Elements inside nuclear power plants. It presents the development of welding processes using coated electrode, SMAW and as addition metal rods EAS 2-IG / ER 308L. This study is divided into two stages, the preparation of technical documentation and the development of methods and manufacturing processes used in the qualification of welding processes. A sequence was outlined based on real situations used by nuclear component manufacturing companies, meeting the physical and mechanical properties required by the nuclear classification standards and their regulations. The results showed that the welding processes were satisfactory, that the destructive and non-destructive tests showed that there was no discontinuity in the surface and defects in the volume of the welding and that, in the present study, safety in the project for the operation of a Nuclear Power Plant was demonstrated.